Impact of specific serotonin receptor modulation on restricted repetitive behaviors - Alvarez, Bryan D.; Cavazos, Cassandra; Morales, Cheyenne A.; M. Lopez, Shannon; Amodeo, Dionisio A. (Frontiers in Behavioral Neuroscience, 2022)
Restricted, repetitive behaviors (RRBs) are commonly divided into two behavioral categories, lower-order and higher-order RRBs. Individuals displaying lower-order motoric RRBs may express repetitive hand flapping behaviors, body rocking back and forth movements, and continuous body spinning. Higher-order RRBs most commonly cover the behavior inflexibility and cognitive rigidity commonly found in disorders such as autism spectrum disorder and obsessive-compulsive disorder. Various neuropsychiatric disorders are plagued by RRBs yet no FDA-approved treatments have been identified. In rodents, lower-order RRBs are commonly measured through various tasks, such as repetitive self-grooming, marble burying, and stereotypic motor behaviors. This review focuses on the effects that modulation of specific serotonin receptors have on lower-order RRBs. Although there is research examining how changes in 5-HT1A, 5-HT1B, 5-HT2A, 5-HT2B, 5-HT2C, 5-HT3, 5-HT6, and 5-HT7 receptor modulation, more research has focused on the 5-HT1A, 5-HT2A, and 5-HT2C receptors. The accumulating data suggest that increasing 5-HT1A activation decreases RRBs while blocking 5-HT1A activation has no effect on RRBs. While there are mixed findings regarding the impact of 5-HT2A modulation on RRBs, the general trend shows mixed effects of 5-HT2A receptor activation RRB expression, whereas blockade generally decreases RRBs. 5-HT2C receptor activation can modulate RRBs in either direction depending on the 5-HT2C drug used, blocking 5-HT2C activation only seems to show therapeutic properties when 5-HT2C activation is already elevated. The other 5-HT receptors have been explored far less but show promise as potential targets for regulating RRBs. Although it is less clear due to the involvement of 5-HT1D, 5-HT1A activation increases RRBs, and blocking 5-HT1A tends to decrease RRBs. 5-HT2B activation could reduce RRBs, while inhibiting 5-HT2B does not impact RRBs. Increasing 5-HT3 has not been shown to affect RRBs. Yet, increases in RRBs have been observed in Htr3a KO mice. 5-HT6 receptor activation can increase RRBs, while blocking 5-HT6 activity tends to decrease RRBs. Lastly, neither increasing or blocking 5-HT7 activity can reduce RRBs. In sum, there is no uniform pattern in whether all specific 5-HT receptors affect RRBs in either direction, instead, there is evidence suggesting that different 5-HT receptors can modulate RRBs in different directions. Further researching the less explored receptors and aiming to understand why these receptors can differently modulate RRBs, may play a key role in developing therapeutics that treat RRBs.